Descriptive Study On Student Interaction In Writing Class At The Seventh Year Of SMP Negeri 3 Sawit In 2013/2014 Academic Year - Alistinawati., Nofita Dwi, Djoko Srijono, M. Hum, Aryati Prasetyarini, S.Pd, M.Pd (2014)
The subject of this descriptive research is the seventh year of SMP N 3 SAWIT in 2013/2014 academic year. The objectives of this research are: (1) to identify the interaction between the student and the teacher in writing class at the seventh year of SMP N 3 Sawit Boyolali, and (2) to identify the problems faced by the teacher in writing class at the seventh year of SMP N 3 Sawit Boyolali. The writer conducts descriptive qualitative research. The writer gets the data of this research from event, informant, and document. The events in this research are all of the activities occured in writing class. The informants are the English teacher and the students of seventh year of SMP Negeri 3 Sawit Boyolali. Documents are all of the written information related to the interaction in writing class. The method of collecting data is observation, interview, and document analysis. After analyzing data, the researcher finds the teacher-students interaction in writing is good. The writer finds the students' interaction in writing class are interaction of the students with the teacher and group interaction. The writer finds the problem faced by the teacher were the students are less open-minded and the students' indolence. The problems faced by the students are limited vocabulary and grammar mastery.